Cerium-Doped Self-Assembling Nanoparticles as a Novel Anti-Oxidant Delivery System Preserving Mitochondrial Function in Cortical Neurons Exposed to Ischemia-like Conditions - Valeria Nele; Valentina Tedeschi; Virginia Campani; Raffaella Ciancio; Alessia Angelillo; Sossio Fabio Graziano; Giuseppe De Rosa; Agnese Secondo (Antioxidants, 2023)
Neurodegenerative diseases are characterized by mitochondrial dysfunction leading to abnormal levels of reactive oxygen species (ROS), making the use of ROS-scavenging nanomaterials a promising therapeutic approach. Here, we combined the unique ROS-scavenging properties of cerium-based nanomaterials with the lipid self-assembling nanoparticles (SANP) technology. We optimized the preparation of cerium-doped SANP (Ce-SANP) and characterized the formulations in terms of both physiochemical and biological properties. Ce-SANP exhibited good colloidal properties and were able to mimic the activity of two ROS-scavenging enzymes, namely peroxidase and super oxide dismutase. Under ischemia-like conditions, Ce-SANP could rescue neuronal cells from mitochondrial suffering by reducing ROS production and preventing ATP level reduction. Furthermore, Ce-SANP prevented mitochondrial Ca2+ homeostasis dysfunction, partially restoring mitochondrial Ca2+ handling. Taken together, these results highlight the potential of the anti-oxidant Ce-SANP platform technology to manage ROS levels and mitochondrial function for the treatment of neurodegenerative diseases.